Nativised English lexemes and semantic shift in Malaysian English / Nur Fatima Wahida Mohd Nasir - Mohd Nasir, Nur Fatima Wahida (Universiti Teknologi MARA, 2021)
Research suggests that Malaysian English (ME) is nativised at all linguistic levels and is especially dynamic at the lexical level. Even the standard form of ME demonstrates an inclination for lexical level nativisation in the form of borrowings, loan translations and new English compounds. Most research in ME lexis has mainly focused on identifying and explaining the evolution of the nativised forms. The frequency of these lexical items and their meanings in the context of use however, have not received much research attention. Thus, the current study addresses this gap based on a descriptive cross-sectional research. The data was analysed based on the six categories of lexicalisation in ME including polysemic variation, semantic restriction, informalization, formalization, directional reversal and college colloquialism. The findings suggest that nativised English lexemes in the category of informalization in ME are most common and that respondents agree on the localised meanings of these lexemes. Nonetheless, there is evidence that some words could also have other meanings in ME, suggesting that meanings of nativised English lexemes are continuously shifting.